Effect of Fast Freeze-Thaw Cycles on Mechanical Properties of Ordinary-Air-Entrained Concrete - Huai-shuai Shang; Wei-qun Cao; Bin Wang (The Scientific World Journal)
Freezing-thawing resistance is a very significant characteristic for concrete in severe environment (such as cold region with the lowest temperature below 0°C). In this study, ordinary-air-entrained (O-A-E) concrete was produced in a laboratory environment; the compressive strength, cubic compressive strength of C50, C40, C30, C25, and C20 ordinary-air-entrained concrete, tensile strength, and cleavage strength of C30 ordinary-air-entrained concrete were measured after fast freeze-thaw cycles. The effects of fast freeze-thaw cycles on the mechanical properties (compressive strength and cleavage strength) of ordinary-air-entrained concrete materials are investigated on the basis of the experimental results. And the concise mathematical formula between mechanical behavior and number of fast freeze-thaw cycles was established. The experiment results can be used as a reference in design, maintenance, and life prediction of ordinary-air-entrained concrete structure (such as dam, offshore platform, etc.) in cold regions.